2005
DOI: 10.1037/0735-7028.36.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Fostering a Culture Shift: Assessment of Competence in the Education and Careers of Professional Psychologists.

Abstract: What is professional competence and how should it be assessed? Professionalism in psychology requires the habitual and judicious use of knowledge and skills as well as ongoing assessment. The authors synthesize discussions of the Assessment of Competence Workgroup that met during the Competencies Conference: Future Directions in Education and Credentialing in Professional Psychology. The workgroup discussed how to establish a culture of competence and elaborated principles and considerations necessary for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
303
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(307 citation statements)
references
References 35 publications
4
303
0
Order By: Relevance
“…Interestingly, the conceptualization of competence in professional psychology has only recently received attention, as a part of what is now termed the competencies-based movement in psychology Roberts et al 2005). The competencies-based movement is a paradigmatic shift occurring in professional psychology that promotes the understanding, education, and assessment of professional competence in psychological practitioners (Roberts et al 2005).…”
Section: Therapist Competence and Competenciesmentioning
confidence: 99%
“…Interestingly, the conceptualization of competence in professional psychology has only recently received attention, as a part of what is now termed the competencies-based movement in psychology Roberts et al 2005). The competencies-based movement is a paradigmatic shift occurring in professional psychology that promotes the understanding, education, and assessment of professional competence in psychological practitioners (Roberts et al 2005).…”
Section: Therapist Competence and Competenciesmentioning
confidence: 99%
“…The fi eld at large has become increasingly aware of the need for more comprehensive models for assessment of professional competencies Roberts, Borden, Christiansen, & Lopez, 2005 ). The fi eld has historically endorsed the assessment of entry -level professional competencies , and Roberts and colleagues (1998) have articulated specifi c " exit criteria " (p. 299) for trainees at various levels (e.g., after completion of graduate training, internship, and post -doctoral training).…”
Section: Training I Ssues/ C Ompetenciesmentioning
confidence: 99%
“…In this regard, professional competency is not viewed as something that is achieved during training and before licensure, but rather as a career-long endeavor that necessitates ongoing assessment of competencies. This viewpoint is shared by the Assessment of Competence Workgroup that met during the 2002 Competencies Conference, which concluded that assessment of competencies should occur throughout the career life span (Roberts et al, 2005).…”
mentioning
confidence: 99%
“…Although varying definitions of professional competence exist, most include reference to competency being essential for the protection of the public (e.g., National Council of State Boards of Nursing, 1996), which requires the accurate mastery of specific skills (e.g., Durley, 2005;Epstein & Hundert, 2002;Roberts, Borden, Christiansen, & Lopez, 2005;Rodolfa et al, 2005).…”
mentioning
confidence: 99%